Development of nutrient management strategies based on mapping of nitrogen flows and balances in dairy production systems in Uganda - Mubiru, L.S.; Romney, Dannie L.; Halberg, N.; Tenywa, J.S. (Elsevier, 2011)
Knowledge of status of nutrient management in agricultural production systems is critical in the development of sustainable improvement options; however, in mixed dairy-crop systems in Uganda, which are gaining prevalence, the status of nutrient management is unclear. Nitrogen (N) being one of the most critical nutrients for agricultural production, studies were done to assess its management in Herding, Tethering, Fenced, Semi-intensive and Zero grazing dairy systems. Data were collected on transfers of materials to obtain N balances on basis of the farm as an entity (“Farm” balances) and for areas under a specific crop or crop mixture (“Cropping Area” balances). Nitrogen balances were mainly negative with positive “Farm” balances featuring only for Zero grazing (16–35 kg ha− 1 season− 1) and Tethering (12 kg ha− 1 season− 1) and positive “Cropping Area” balances only within the Tethering category (1 kg ha− 1 season− 1). Most inefficient utilization of N was within the Zero grazing category where the difference between the “Farm” and “Cropping Area” balances was 55 kg ha− 1 season− 1. Nitrogen input requirements into the “Cropping Areas” to off-set negative N imbalances were in the ranges of 207–2143 kg ha− 1 season− 1 of cattle manure equivalent to 6–60 kg ha− 1 season− 1 of urea.